Self-reported symptoms experienced by intensive care unit patients: a prospective observational multicenter study - Christin Saltnes-Lillegård; Tone Rustøen; Sigrid Beitland; Kathleen Puntillo; Milada Hagen; Anners Lerdal; Kristin Hofsø (2023)
The purpose of this study is to describe the prevalence, intensity and distress of five symptoms in intensive care unit (ICU) patients and to investigate possible predictive factors associated with symptom intensity.This is a prospective cohort study of ICU patients. A symptom questionnaire (i.e., Patient Symptom Survey) was used to describe the prevalence, intensity and distress of pain, thirst, anxiousness, tiredness, and shortness of breath over seven ICU days. Associations between symptom intensity and possible predictive factors were assessed using the general estimating equation (GEE) model.Out of 603 eligible patients, 353 (Sample 2) were included in the present study. On the first ICU day, 195 patients (Sample 1) reported thirst as the most prevalent symptom (66%), with the highest mean intensity score (6.13, 95% confidence interval (CI) [5.7-6.56]). Thirst was the most prevalent (64%) and most intense (mean score 6.05, 95%CI [5.81-6.3]) symptom during seven days in the ICU. Anxiousness was the most distressful (mean score 5.24, 95%CI [4.32-6.15]) symptom on the first day and during seven days (mean score 5.46, 95%CI [4.95-5.98]). During seven days, analgesic administration and sepsis diagnosis were associated with increased thirst intensity. Older age and being mechanically ventilated were associated with decreased pain intensity, and analgesic administration was associated with increased pain intensity. Family visits and female gender were associated with increased intensity of anxiousness and shortness of breath, respectively.Self-reporting ICU patients experienced a high and consistent symptom burden across seven days. Certain variables were associated with the degree of symptom intensity, but further research is required to better understand these associations.